Gender differences in expressing love in marriage – stability across generations and cultures - Huić, Aleksandra (Array, 2011)
Cancian (1986) argued that men and women have been socialized to show love in different ways, with women showing love by expressing positive emotions directly and men by doing activities together, helping out with domestic chores, and showing sexual interest. Furthermore, she argued that integrating both feminine expressivity and masculine instrumentality is what makes a relationship more loving for both men and women. Our aim was to test her ideas by directly asking married couples how they show love. We were interested in gender differences in the ways of showing love, as well as in the stability of these differences between three generations within Croatian and Serbian cultures. We tested 302 Croatian and 350 Serbian married couples whose length of marriage varied between one month and 57 years. Both Croatian and Serbian samples consisted of couples from various urban/rural backgrounds, all levels of education and employment status. Based on their age couples were divided into three groups representing different generations (20–35 y. ; 36-54 y. ; 55-87 y.). We administered the Love Scale (Braiker & Kelly, 1979) and The Ways of Showing Love Scale (Huić, Kamenov & Jugović, 2010). The latter measures 4 expressive („communal orientation/sacrifice“ ; „emotional openness and support“ ; „physical affection“ ; „verbal affection/gifting“) and 2 instrumental factors („domestic instrumentality“ ; „public instrumentality“). Overall results show main effects of love and gender, but no interaction. A significant main effect of love seems to confirm Cancian's androgynous perspective of love - both men and women who love more use more of both expressive and instrumental ways of showing love than do men and women who love less. Expectedly, it is more characteristic for women than for men to show love by doing housework and being supportive. Showing love with physical affection and running errands is more characteristic for men. Contrary to Cancian, there are no gender differences when it comes to verbally showing affection or putting one's needs before partner's. The stability of patterns of gender differences was tested for couples from different generations and cultures. Although most of the patterns remained the same, some interesting findings supported our expectations about the effect of socialization and cultural influences.